Effect of IT capability and intangible IT resources on sustainable competitive advantage: Exploring moderating and mediating effect of IT flexibility and core competency - Lahcene Makhloufi; Noorulsadiqin Azbiya Yaacob; Abderrazak Ahmed Laghouag; Alhussain Ali Sahli; Fateh Belaid (Cogent Business & Management, 2021)
The purpose of this research is (1) to examine the integration impact of IT assets (e.g., intangible IT resources, IT capability, and IT flexibility) on core competency, and (2) to explore the mediating effect of core competency on the relationship between IT assets and sustainable competitive advantage (SCA), and (3) to determine whether IT flexibility strengthen the relationship between core competency and SCA. The study applied a quantitative and cross-sectional approach to collect data from 164 Malaysian small and medium-sized enterprises (SMEs) targeting managers from the middle-to-upper level. The findings infer new insights regarding IT integration's critical role within core competency activities to achieve SCA. The results show that IT assets possess a positive and significant impact on core competency (CC), and CC positively impact SCA. Finally, CC partially mediates the relationship between IT resources and IT capability to SCA, and IT flexibility positively moderates the relationship between CC and SCA. This study addressed IT's integration within core competency activities to help SMEs achieve SCA. The study advances dynamic capability theory by providing new insights into the importance of core competency and IT integration to develop and reconfigure existing capabilities to fit business strategy goals.
Keywords: 650; Sustainable competitive advantage; Core competency; IT flexibility; ITcapability; Intangible IT resources; Dynamic capability theory; Malaysian SMEs